2018
DOI: 10.3390/su10051316
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for Environmentally Friendly Products among Low-Income Households along Coastal Peninsular Malaysia

Abstract: In an attempt to promote the mass consumption of environmentally friendly products in Malaysia, this study presents an investigation of the effects of several selected factors upon willingness to pay and purchase behavior of environmental-friendly products. This study employed a cross-sectional design, in which quantitative data were gathered from a total of 380 low-income household heads from 38 coastal districts in Peninsular Malaysia. The outcomes of this study revealed the positively significant effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
60
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 48 publications
(132 reference statements)
8
60
1
1
Order By: Relevance
“…This research shows that, consumers do not believe that the money they pay can reduce the impact of environmental damage. The results of this study reject the results of research byMamun et al (2018) which states that consumer knowledge of product benefits has a positive effect on product purchases. On the contrary, the results of the study are strengthened by the results of previous studies byWen and Hwang (2018) which state that Reasonable & Objective is not the reason consumers are willing to pay for green services.…”
contrasting
confidence: 99%
“…This research shows that, consumers do not believe that the money they pay can reduce the impact of environmental damage. The results of this study reject the results of research byMamun et al (2018) which states that consumer knowledge of product benefits has a positive effect on product purchases. On the contrary, the results of the study are strengthened by the results of previous studies byWen and Hwang (2018) which state that Reasonable & Objective is not the reason consumers are willing to pay for green services.…”
contrasting
confidence: 99%
“…However, based on the finding by [43] provided that if the consumers are willing to agree and pay extra charges, the higher pricing impediments will not distract green products adoption. The previous study confirmed that the consumers are willing to pay for greener products [2], [10], and [22]. Therefore, it is hypothesized that:…”
Section: Willingness-to-pay (Wp)mentioning
confidence: 72%
“…TPB is a frequently employed framework to illuminate human behaviors and to envisage individual's intention to involve in behavior at an explicit place and time. TPB has been widely used in different researches [2], [8], [21], [25], [27], [37], [38], [42]. The intention is frequently applied as a proxy for predicting future behavior as individuals with sturdier intention will likely execute it [40].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is also considered a crucial predictor of purchase behavior. In the organic industry, it has been found that consumers with a high awareness of environmental issues are more likely to consume organic food [20]. Notarnicola et al…”
Section: Motives Of Willingness To Buy Organic Foodmentioning
confidence: 99%